If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(a-2)=2a+3
We move all terms to the left:
4(a-2)-(2a+3)=0
We multiply parentheses
4a-(2a+3)-8=0
We get rid of parentheses
4a-2a-3-8=0
We add all the numbers together, and all the variables
2a-11=0
We move all terms containing a to the left, all other terms to the right
2a=11
a=11/2
a=5+1/2
| -17-12.74=-15.4h+18.62 | | 81^x=1/27 | | -12=-6+3u | | 5(x+1)+35=-3x | | 6=3/7w | | 6=3/4w | | (4x+6)+(2x-10)=44 | | 7-y/2=21 | | 20x-4=3(4x+2) | | 4x^2/5-x/5-3/10=0 | | 22–3y=1 | | 6x+4x-15=30-5x | | 11/x=8/3 | | x^+2x+1=0 | | 3x-6=30-x | | 2=3n+1/2 | | 30+(3c+4)=2(c+7)+c | | N=g(-2)+3 | | 12x=14=12x+5 | | -16w+14+4w=-14w-16 | | 7x÷3=2x-12 | | 3=5z+18 | | 11+3a=-15-4a | | t÷3-8=9 | | 45-5t=25 | | 7(x+5=-7(x+5) | | -2a+14=44* | | 4x+5x-42=70 | | 6x+7x-68=34-4x | | 4(x-4)=8(2x-14) | | -3-5d=14+12d | | 14x+8=48 |